ARTIFICIAL INTELLIGENCE IN ADAPTIVE LEARNING TO ACCOMMODATE STUDENT DIVERSITY - Arsyad, Susalti Nur; Dipalaya, Tismi; Muriati, St (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
The development of Artificial Intelligence (AI) has brought significant transformation to the world of education, especially in the implementation of adaptive learning that is able to accommodate the diversity of characteristics of elementary school students. This diversity includes differences in cognitive abilities, learning styles, socio-cultural backgrounds, and learning pace. This study aims to analyze the implementation and effectiveness of the use of Artificial Intelligence in adaptive learning at Athirah Racing Center Islamic Elementary School as an effort to improve the quality of inclusive and student-centered learning. This study uses a descriptive qualitative approach with research subjects including classroom teachers, students, and the principal. Data were collected through classroom observations, in-depth interviews, and documentation. The results of the study show that the use of AI in adaptive learning can help teachers map students’ individual learning needs, provide recommendations for materials that are appropriate to students’ ability levels, and increase student engagement and learning motivation. Furthermore, AI functions as a tool to support more accurate and data-driven pedagogical decision-making. However, this study also identified several challenges, including limited teacher digital literacy, technological infrastructure, and the need to strengthen the ethical and supervisory aspects of AI use in elementary schools. This research is expected to provide theoretical and practical contributions to the development of AI-based adaptive learning in Islamic elementary schools, oriented toward strengthening character and Islamic values.